Strengthen of magnetic anisotropy of Au/Co/Au nanostructure by surface plasmon resonance - Yusuke Kikuchi (Nature Portfolio, 2019)
Abstract We experimentally demonstrated the increase of in-plane magnetic anisotropy in Au/Co/Au nanostructures by localized surface plasmon resonance (LSPR). When an array of Au/Co/Au square patch nanostructures was illuminated with linearly polarized light whose wavelength was 750 nm, the localized surface plasmons were resonantly excited in the nanostructures. From the measurement results of polar magneto-optical Kerr effect curves, we observed the magnetic anisotropy field increase in the Au/Co/Au nanostructure due to the excited surface plasmons. The in-plane magnetic anisotropy energy density was increased about 24%.